Kebijakan dan Implementasi Program Pelatihan Kejuruan bagi Anak Jalanan di Kabupaten Subang - Tera Ummuttaufiqoh; Hendi Suhendraya Muchtar; Supyan Sauri (University of Muhammadiyah Malang, 2021)
The increasing number of street children in Subang Regency became a social problem that it raised questions about the government’s role in handling street children. The purpose of this research was to examine the policy and implementation of the Subang Regency Social Services program in fostering street children through vocational training, as well as to examine the problems of implementing vocational training, and what attempts were made toovercome these problems. The theory of constructivism supported this research because it was expected that street children would be able independently to form the knowledge that has been previously acquired and then combined it with the new knowledge gained in vocational training. This research procedure used a qualitative descriptive methodin the form of case study research. The results of the research on program policies and the implementation of vocational training for street children were not carried out directly at the Social Services, due to several problems, including limited budgets, Regional Regulations have not been published yet and inadequate infrastructure, so that it needed an attempt to overcome the problems that was collaboration with Ministry of Social Affairs that wasPPSBR institution (Panti Pemberdayaan Sosial Bina Remaja) which is located in several cities/districts. In conclusion, the policy of the Subang Regency Social Services program is not capable to realize coaching optimally through vocational training for street children.